Desativação do deoxinivalenol em grãos de trigo com gás amônia e seu efeito na dieta de frangos de corte - Ferreira, Jaine Mendes (2023)
On the world stage, Brazil is a major producer of wheat and broilers. The states of southern Brazil, Rio Grande do Sul, Santa Catarina and Paraná, comprise most of the wheat production in the country and are also the largest poultry producers. Wheat is a food widely used for animal and human consumption. Giberella, a disease caused by the fungus Fusarium gramineaium in wheat, stands out for being difficult to control and capable of producing a highly toxic mycotoxin known as Deoxynivalenol (DON). This toxin remains viable in wheat grains, even after processing, and is likely to be consumed by humans in wheat-derived foods and also by animals, leading to acute, subacute and cumulative clinical signs. The National Health Surveillance Agency, with the Collegiate Board Resolution (RDC) nº 7, reduced the maximum tolerated limits (LMT) for mycotoxins, such as Deoxynivalenol (DON) in wheat grains, processed wheat, barley and rice. The high incidence of fungal growth in regions with higher humidity, where the largest cereal plantations are located in Brazil, compromises production and raises the levels of mycotoxin found in wheat, sometimes reaching the maximum limit for human consumption. The use of wheat contaminated with DON for animal feed translates into a zootechnical result with significant losses. Among the different existing methods for deactivating mycotoxins, ammonia gas has proven to be the most efficient. The objective of this study was to evaluate the zootechnical result of broiler chickens fed wheat grains that underwent ammonization at a concentration of 1%. The experiment was approved by the Committee on Ethics in the Use of Animals of the University of Passo Fundo (CEUA-UPF) number 023/2022. The experiment was conducted by evaluating the control group (Untreated wheat) in relation to the treatment (Ammonized wheat). Each treatment was repeated 4 times, using 6 birds (3 males and 3 females) in each repetition. The inclusion of wheat in the diets started at 21 days of age until the birds were slaughtered. The evaluated parameters were: the weight gain of the animals, the feed conversion and the histopathological evaluation of the liver and intestine. According to the results obtained, the groups that received diet with ammoniated wheat had better feed conversion (p<0.05) compared to the control group; 1.41 at 42 days, 1.49 at 48 days and 1.53 at 42 days, 1.58 at 48 days, respectively. As for the daily weight gain, there was no statistical difference between birds that consumed ammonized wheat and control. In the histopathological evaluation of the small intestine and liver of broilers, those that received ammoniated wheat showed better integrity of the intestinal villi and less hepatic degeneration compared to the control group. Thus, the results of this work showed that ammonized wheat did not interfere with daily weight gain, improved feed conversion and integrity of intestinal villi in broiler chickens.